UKM SEBAGAI KOMPONEN PENGEMBANGAN DESA WISATA YANG BERKELANJUTAN - Danang Yudhiantoro; Eny Endah Pujiastuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Community service performed in SMEs snacks Pentingsari tourist village, because SMEs are an important component for the tourist village pentingsari. Mentoring Approach used was developed bisnis.mentoring program, the increase in productivity of SMEs, improving product quality, packaging, distribution channels. In general, community service shows that the improved performance of SMEs will increase incomes, consumers become satisfied, the emergence of a good business climate. With the community service activities by the college will create partnerships between SMEs and universities. Keywords: UKM, Mentoring, partnerships, distribution Channels, tourist village